Doping investigation of structured GaN devices by highly lateral resolved TOF-SIMS - Patrick Diehle; Stephan Gierth; Mickael Lejoyeux; Karen Geens; Matteo Borga; Frank Altmann (Power Electronic Devices and Components)
The measurement of doping concentrations is a fundamental need for the development and processing of power electronic devices like normally-off semi-vertical GaN trench MOSFETs. We employed highly laterally resolved TOF-SIMS to evaluate the doping levels of the n- and p- doped layers close to the gate trench. A lateral resolution of approx. 100 nm was achieved sufficient to resolve the gate trench geometry. Furthermore, the analysis and the visualization of the 3D data was optimized by implementing the correction of the topography and image distortions. No change of the Mg and Si doping of the n- and p- layers close to gate trench sidewall was observed.